Educação de Jovens e Adultos: representações de professores e alunos sobre ensino aprendizagem de inglês - Aneas, Flávio (2010)
This research has aimed to investigate the representations which teachers and students of adult and young adult education have about English Language teaching-learning and, by comparing them to each other, find convergences and divergences that might point out any kind of tendency. The research is grounded on the social representation theory, based on Moscovic (2003), Farr (1995), Minayo (1995), and Celani e Magalhães (2002), among others. It is also grounded on adult and young adult students different concepts, the factual and legal history of this education segment in Brazil based on official documents and scientific articles, as well as on the most well known and diffused teaching-learning theories in this country. The research has followed the case study methodological frame (JOHNSON, 1992, e STAKE, 1998) and has been developed among four of the Guarulhos city government schools, located in São Paulo state, Brazil. 3 teachers and fourteen students of adult and young adult classes (fifth to eighth grades) have participated in the research, whose data were collected through questionnaires in November, 2009. The results showed to exist convergences into the Socio-intereactionist teaching-learning theory among the representations of teachers and students and also divergences from this focus in some of the students representations which seems to present traditional characteristics. Because representations with Socio-interacionist characteristics are present in a larger number and because of the action of the representations, there seems to be a tendency of diminishing the number of Socio-interationist diverging representations